Analisis getaran lambung kapal patroli 28 meter - Amalia Ika Wulandari; Alamsyah Alamsyah; Muhammad Fikri Fadlurrahman (TURBO [Tulisan Riset Berbasis Online], 2022)
The ship's vibration is something that has a considerable influence on the structural resistance and comfort of the crew. Vibration analysis needs to be done to ensure the durability of the ship's construction. Ship construction that is unable to withstand the vibrations it experiences is at great risk of structural failure. Vibration on the ship is also something that can only be suppressed and cannot be completely eliminated. The objectives to be achieved in this final project are to get the value of the ship's resistance and get the root-mean-square value of the maximum vibration speed that occurs on the ship. The calculation of the value of the ship's resistance is carried out using the Holtrop resistance calculation method, while the determination of the root-mean-square maximum speed of vibration is carried out using the Ansys Workbench. The resistance value obtained on this ship is 7,165 kN. The root-mean-square value of the greatest maximum vibration velocity occurs at a frequency of 47.2 Hz at 76.71906943 m/s. Due to the limit value of r.m.s for aluminum vessels is 15 mm/s, then the value of r.m.s at a frequency of 47.2 Hz that occurs on ships does not meet class standards.